Risk and protective factors for alcohol use disorders across the lifespan - Deeken, Friederike; Banaschewski, Tobias; Kluge, Ulrike; Rapp, Michael A. (Current addiction reports, 2020)
Losing and regaining control over alcohol intake varies as a function of individual-level predictors across the lifespan. Specifically, the interplay of protective and risk factors for losing and regaining control, particularly in real-life settings, is thus far poorly understood. Individual differences in cognition, affect, emotion regulation, social factors, and personality traits, together with individual differences in brain structure and function, and biological markers of stress exposure may have different effects on alcohol consumption in different age groups. We will review current evidence for age-specific effects for losing and regaining control over alcohol intake and propose a framework for investigation across age groups.
Gesehen am 11.11.2025